Achilles tendinitis - Prevention and treatment - Brandon, R.; Watson, A.; Haddad, F.; Reynolds, W. (Peak Performance, 2002)
Achilles tendinitis is a painful and debilitating injury with sometimes serious consequences. It can become so severe that many athletes undertake surgery to correct the condition. There are, however, some common misconceptions about the condition. This book explains the causes of the injury, how to avoid it and gives exercises to get an injured ankle fully functional once more. PREVENTION PROGRAMME: We look at the causes of Achilles tendinitis, and outline an exercise strategy that will make your Achilles as strong as spun steel (Raphael Brandon) TECHNICALLY SPEAKING: Here`s a further look at Achilles tendinitis, this time from a surgeon`s point of view (Alex Watson and Fares Haddad) STRENGTHENING PROGRAMME: Achilles tendinitis is the curse of the running classes. If you suffer from it, these exercises should help prevent it happening again (Raphael Brandon) ANKLE STRENGTHENING: Weak ankles are a key factor in causing Achilles tendinitis. Here`s a guide to making them strong and proof against sprains as well (Walt Reynolds) ABOVE THE ANKLE: Here`s how to get an injured knee fully functional once more (Raphael Brandon) WHAT THE PAPERS SAY: Having a short Achilles tendon may be an athlete`s Achilles heel